Pengaruh Tingkat Literasi Keuangan Dan Pembelajaran Di Perguruan Tinggi Terhadap Perilaku Keuangan Mahasiswa - Agung, Eka Adnan; Oktarina, Harti; Bungatang, Bungatang (Universitas Negeri Makassar, 2021)
This study aims to determine the effect of financial literacy and learning in higher education on the financial behavior of students in the Economic Education STKIP Indonesian development, both partially and simultaneously. This study uses a quantitative approach. The population in this study were students of the Economic Education STKIP Indonesian Development. The sampling technique in this study used the Slovin formula so that the sample was 122 students. The method of collecting data using a questionnaire. Before the questionnaire is distributed first and the test results state the questionnaire is valid and reliable. The data analysis technique used is multiple regression techniques. The simultaneous test results show that Financial Literacy and Learning in Higher Education have a significant effect on the Financial Behavior of Economic Education Students of STKIP Pembangunan Indonesia. The partial test results show that: 1) Financial literacy affects financial behavior with a sig. 0.026 <alpha value (0.05); 2) Learning in Higher Education affects Financial Behavior with a sig value of 0.000 <alpha value of 0.05. The results of the coefficient of determination test show that financial behavior is explained by the variables of financial literacy and learning by 25.5% and 74.5% by other variables.